Flow balancing in extrusion dies for complex geometry profiles - Gonçalves, N. D. (2012)
This work describes a numerical code, able to deal with unstructured meshes, developed to solve the Navier-Stokes equations, and its employment to aid the design of an extrusion die used on the production of a complex cross section profile